دراسة مقارنة للصورة المدركة من المستهلك الجزائري لكل من الجزائر، اليابان و الصين كبلدان منشأ للمنتجات الإلكترونية - مجاهدي, فاتح (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
With the increasing openness of the Algerian market to international markets as well as the increasing intensity of competition facing the Algerian products, especially with the high level of awareness of the Algerian consumer in his shopping manners, which has become more demanding in terms of quality and social image of the purchased product. Under all these circumstances, the required and the obtained information become an important factor to evaluate products and brands especially in the case of technically complex products, such as electronic ones, which might be evaluated using a specific kind of information and indexes like brands and country of origin of the product, which has many dimensions such as country of origin image, or the attitude toward country of origin. Accordingly, the country of origin becomes the most important indicators used in the evaluation of product, thus the problem of this research can be asked as follow: What’s the perceived COO image from the Algerian consumer of Algeria as electronics COO Vs Japan and China?